2008
DOI: 10.1186/1471-213x-8-104
|View full text |Cite
|
Sign up to set email alerts
|

The DrosophilaSTIM1 orthologue, dSTIM, has roles in cell fate specification and tissue patterning

Abstract: Background: Mammalian STIM1 and STIM2 and the single Drosophila homologue dSTIM have been identified as key regulators of store-operated Ca 2+ entry in cells. STIM proteins function both as molecular sensors of Ca 2+ concentration in the endoplasmic reticulum (ER) and the molecular triggers that activate SOC channels in the plasma membrane. Ca 2+ is a crucial intracellular messenger utilised in many cellular processes, and regulators of Ca 2+ homeostasis in the ER and cytosol are likely to play important roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 101 publications
3
16
1
Order By: Relevance
“…Whereas for the locus at 50 cM, there is a mounting indication that the causal mutation might be located within or near the NCAPG gene, the genetic background of the putative second QTL at position 55 cM remains open. Although peroxisome proliferator-activated receptor gamma, coactivator 1 alpha (PPARGC1A) and stromal interaction molecule 2 (STIM2) are candidate genes for fetal growth due to their function in energy metabolism and embryonic development (Puigserver and Spiegelman 2003;Eid et al 2008), our data do not convincingly support a causal role of either gene regarding genetic modulation of fetal growth. Further research is necessary to elucidate the background of the second QTL affecting fetal growth.…”
Section: Discussioncontrasting
confidence: 51%
“…Whereas for the locus at 50 cM, there is a mounting indication that the causal mutation might be located within or near the NCAPG gene, the genetic background of the putative second QTL at position 55 cM remains open. Although peroxisome proliferator-activated receptor gamma, coactivator 1 alpha (PPARGC1A) and stromal interaction molecule 2 (STIM2) are candidate genes for fetal growth due to their function in energy metabolism and embryonic development (Puigserver and Spiegelman 2003;Eid et al 2008), our data do not convincingly support a causal role of either gene regarding genetic modulation of fetal growth. Further research is necessary to elucidate the background of the second QTL affecting fetal growth.…”
Section: Discussioncontrasting
confidence: 51%
“…This induces apoptosis and reduces cell-cell adhesion (Mekahli et al, 2011). Smaller, blistered wings with thicker veins have been reported when SERCA, Stim or Orai is inhibited (Balaji et al, 2017;Eid et al, 2008;Restrepo and Basler, 2016). We confirmed that knocking down SERCA, Stim, and Orai led to smaller, blistered wings when driven by nub ( Fig.…”
Section: Oscillatory Ca 2+ Signal Exhibits Four Categories Of Ca 2+ Asupporting
confidence: 81%
“…Destabilizing the homeostatic concentrations of Ca 2+ in the ER and the cytoplasm influences Ca 2+ signaling differently than disrupting transient phenomena such as Ca 2+ release. SOC channels have been implicated in the control of growth and patterning in wing disc development (Eid et al, 2008;Richard and Hoch, 2015). Interestingly, knockdown of SOC channel components did not strongly impact ICT frequency.…”
Section: Discussionmentioning
confidence: 98%
“…Stim1, which couples ER-PM Ca 2+ flux in mammals, is also highly conserved in flies and is essential for proper larval development and mechano-sensory bristle differentiation. 32,33 The yeast enoyl-reductase Tsc13 that localizes to ER-vacuole NVJs in yeast is conserved in flies as Sc2, whose loss is embryonic lethal. Mutant Sc2 alleles have also been shown to exacerbate fly models of spinocerebellar ataxia.…”
Section: Organelle Contact Site Proteins In Drosophila mentioning
confidence: 99%